Using virtual fieldwork to support interprofessional and community-based learning: students from four faculties investigate life on a remote island in Japan - Yatsushiro, Rika; Matsuda, Fumiyo; Causer, Bo; Inoue, Kazuhiro; Kikata, Junne; Miura, Naoki; Hashimoto, Kumiko; Akasaki, Yasuaki; Unedaya, Keiko (Frontiers in Education, 2024)
The Mishima Islands in Kagoshima Prefecture, Japan, are remote islands designated as medically underserved. Supporting the people living in such remote islands requires a multifaceted examination of the livelihoods of the residents, including their health, work, and living environment.Methods: Using the lens of the United Nations SDGs, students from the faculties of nursing, veterinary science, agriculture, and engineering participated in a three-day virtual fieldwork session held synchronously from the campus of Kagoshima University and on a remote island in the Mishima Mura island group in Kagoshima Prefecture, Japan. Coursework and post-course surveys were analyzed to determine student engagement and learning. In particular, the analysis considered learning in relation to interprofessional learning and community-based learning.Students expressed being able to conduct fieldwork online, collaborate with students from multiple faculties and graduate schools, and apply their expertise. These outcomes were reflected in the 5-point Likert scale evaluation responses, highlighting a sense of accomplishment and satisfaction. Virtual fieldwork can contribute to student learning by introducing new concepts and allowing them to consider development issues in remote areas from multiple perspectives.コメントの追加 [A1]: We will update the word count once the Manuscript is completely finalized. 削除: 2 123 削除: learning (IPL) and community-based learning (CBL). 124 Knowledge of these practices significantly influences the 125 development of the course and provides a framework for assessing 126 course outcomes.